2011
DOI: 10.1016/j.actbio.2010.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of a phosphonated analog of matrix phosphoproteins within cross-linked collagen as a templating mechanism for biomimetic mineralization

Abstract: Immobilization of phosphoproteins on a collagen matrix is important for induction of intrafibrillar apatite mineralization. Unlike phosphate esters, polyphosphonic acid has no reactive sites for covalent binding to collagen amine groups. Binding of polyvinylphosphonic acid (PVPA), a biomimetic templating analog of matrix phosphoproteins, to collagen was found to be electrostatic in nature. Thus, an alternative retention mechanism was designed for immobilization of PVPA to collagen by cross-linking the latter w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 51 publications
0
79
0
2
Order By: Relevance
“…Similar to CHX, PVPA binds electrostatically to collagen. However, its use as a potential MMP inhibitor in dentin bonding may be more advantageous than CHX in that PVPA can be trapped in collagen matrices via the use of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) [101]. These results suggest that the use of PVPA could enhance the longevity of the dentin-resin bonds.…”
Section: Biphosphonatementioning
confidence: 93%
“…Similar to CHX, PVPA binds electrostatically to collagen. However, its use as a potential MMP inhibitor in dentin bonding may be more advantageous than CHX in that PVPA can be trapped in collagen matrices via the use of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) [101]. These results suggest that the use of PVPA could enhance the longevity of the dentin-resin bonds.…”
Section: Biphosphonatementioning
confidence: 93%
“…It seems that phosphorylated extracellular proteins play critical roles in the formation of collagenous mineralized tissues and in the regulation of biomineralization [Deshpande et al, 2011]. However, it has been shown that phosphoproteins are non-specific and may be substituted by other immobilized, naturally occurring phosphoproteins to induce apatite deposition within collagen [Gu et al, 2010]. Phosphorylation of dentin collagen has previously been shown to cause a significant surface remineralization of demineralized dentin [Saito et al, 1998;Bertassoni et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…[ 91,92,135,147,148 ] Polycarboxylic acids such as polyacrylic acid (PAA) or polyaspartic acid were employed as biomimetic NCP analogs for binding and sequestering calcium ions to prevent aggregation of fl uidic ACP nanoparticles and auto-transformation of the ACP nanoparticles into apatite before they enter into the intrafibrillar water compartments of the collagen fi bril. Additionally, polyphosphates including polyvinylphosphonic acid, small 2016, DOI: 10.1002/smll.201600626 Figure 10 .…”
Section: Dual Biomimetic Analog-based Bottom-up Strategy For Hierarmentioning
confidence: 99%